Ashwagandha From Ancient Root to Modern Remedies - Shifa Shaikh; Vaishnavi Jadhav; Gaurav Bhende; Pratik Raul; Ravi Raj Rama Jadhav (International Journal of Progressive Research in Science and Engineering, 2024)
Recent years, there has been an increase in reports on health-promoting properties of winter cherry (Withania somnifera), generally known as Ashwagandha. It is highly regarded Rasayana (tonic) plant in the Indian Ayurvedic medical system for over three thousand years. Although previous review papers on this plant have been published, this review article is offered to gather all of the most recent information on its phytochemical and pharmacological activities, which were conducted using variety of approaches. According to studies, Ashwagandha has antioxidant, anxiolytic, adaptogenic, memory-enhancing, anti-parkinsonian. Anti venom, anti-inflammatory and anti-cancer effects. There were 41 studies that looked at Ashwagandha’s effects on stress and anxiety, sexual function and fertility, athletic performance, cognitive, performance, pain, fatigue, thyroid, function, schizophrenia, diabetes, obsessive-compulsive disorder, insomnia, hyper cholesterol, and tuberculosis. This systemic review suggests that Ashwagandha has a wide range of medicinal application such as immunomodulation, hypolipidemia, antimicrobial, cardiovascular, protection, sexual behavior, tolerance and dependence have been investigated. This growing corpus of research on Ashwagandha demonstrates its promise as a beneficial natural therapy for a review looks into the most recent discoveries and provide a detailed summary of our current understanding of Ashwagandha’s potential uses, as well as any known safety problems and contraindications. Their morphological and anatomical structural have a diagnostic role in taxonomy identification and some adaptive peculiarities may be suitable morphological and anatomical structural have a diagnostic role in taxonomy identification and some adaptive peculiarities may be suitable for Ashwagandha plant successful growth in the relative dry conditions of our region.